Primary Pulmonary Acinic Cell Carcinoma: A Clinicopathological Study of 6 Cases and Literature Review. (September 2019) - Nie, Ling; Zhou, Chunlei; Wu, Hongyan; Zhou, Qiang; Meng, Fanqing
Primary pulmonary acinic cell carcinoma (ACC) is rare. The clinicopathological features are not identical to that of classic ACC that leads to misdiagnosis. In this article, we summarized the clinicopathological features of 25 such cases, including 6 cases in this series and additional 19 cases in the literature. Pulmonary ACCs showed an overwhelming solid growth pattern. The neoplastic cells had eosinophilic granular and clear cytoplasm in most cases and displayed basophilic cytoplasm in only 4 cases. Intratumoral fibrous septa, mitotic figure, necrosis, and psammoma bodies were observed in some cases. Prominent nuclear atypia and perineural invasion might suggest high-grade transformation, metastasis, and recurrence. The tumor cells were strongly positive for CK8/18 and negative for TTF-1, p63, S-100, mammaglobin, MUC5b, MUC5ac, and DOG1. CK7 was exclusively positive for neoplastic cells with ductal differentiation. Of the 25 included cases, 10 cases were initially misdiagnosed. The tumor was prone to involve the right bronchus. The patient outcome was favorable. The accurate diagnosis of primary pulmonary ACC relies on comprehensive evaluation of histological and immunohistochemical features and realization of the difference from classic ACC.